How do they eat: a digital diet ethnography of dietary behavior determinants among New Zealand and Chinese university students - Li, Xingbo; Ariell, Nick; Braakhuis, Andrea; Li, Zengning; Roy, Rajshri (Frontiers in Nutrition, 2026)
BackgroundNon-communicable diseases (NCDs) are a leading cause of global mortality and poor dietary habits are key contributors. University students are especially vulnerable to obesogenic food environments, yet cross-cultural qualitative evidence on how campus and home food environments shape student dietary behaviors is limited. This study used digital diet ethnography to compare determinants of dietary behavior among university students in New Zealand and China.MethodsNine New Zealand and ten Chinese university students recorded their meals and contextual reflections via the Indeemo platform for 90 days. Multimodal data (photos, videos, text) were thematically analyzed using a hybrid inductive–abductive approach informed by cohort-specific theoretical frameworks; coding followed a harmonized content-analysis protocol with double-coding, consensus meetings, and manual verification of automated transcripts.ResultsNew Zealand findings coalesced into four themes: (1) time is of the essence, (2) cash is king, (3) the on-off campus conundrum, and (4) miscellaneous influences. In China three major themes emerged: (1) social and environmental determinants, (2) food-related determinants, and (3) intrapersonal determinants. Clear distinctions exist between on-campus and at-home datasets. Across cohorts, time scarcity, perceived cost, convenience, sensory preferences and social influences were dominant drivers. However, their mechanisms differed according to institutional food systems (marketized options vs. subsidized canteens) and cultural contexts.ConclusionsUniversity students' suboptimal dietary patterns primarily reflect rational, pragmatic responses to shared contextual constraints rather than individual deficits in diet behaviors. The consistency of these constraints across divergent food environments underscores the need for structural interventions that increase the availability, affordability, convenience, and sensory appeal of healthier options while leveraging each system's strengths to make healthy eating the default choice.